Solid state diffusion in Pd₂Si - Egan, John Mathew (Department of Physics, 2016)
The atomic transport processes ocurring in the Pd/Si system have been investigated. The Pd₂Si system has been studied to try and establish the mechanism(s) of diffusion by which the growth of Pd₂Si proceeds under thermal annealing. Using a deposited Ti marker, the dominant moving species during Pd₂Si formation in the temperature range 250-400°C has been determined to be silicon. Palladium transport appears to occur during the initial stages of formation of Pd₂Si. Once several hundred angstrom of Pd₂Si has been formed, palladium transport seems to be replaced by silicon transport. Silicon tracer experiments, in conjunction with Si selfdiffusion measurements. indicate that silicon mobility is exceptionally high during the formation of Pd₂Si on Si substrate. During growth. the mobility of silicon is orders of magnitude higher than under equilibrium conditions. This is thought to suggest a vacancy mechanism of diffusion, and is expected that large numbers of vacancies are generated at the growth interface during silicide formation. Silicon self-diffusion in Pd₂Si has been investigated. The results indicate that grain-boundary diffusion could be operative under equilibrium conditions. Under the assumption that grain-boundary diffusion does occur during thermal annealing in the range 350-550°C, it is deduced that at all times the grain-boundary diffusivity is so much greater than the lattice diffusivity, that the grain-boundaries are effectively able to act as sources for the grains. The activation energy for lattice self-diffusion of silicon in Pd₂Si which has grown on Si<100> substrate, has been determined to be 0.8±0.3eV. This value is thought to support recent kinetic results which indicate that the activation energy for growth of Pd₂Si is in the region of 1eV.